2020
DOI: 10.1007/s10734-020-00561-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and digital disruption in UK universities: afflictions and affordances of emergency online migration

Abstract: COVID-19 has caused the closure of university campuses around the world and migration of all learning, teaching, and assessment into online domains. The impacts of this on the academic community as frontline providers of higher education are profound. In this article, we report the findings from a survey of n = 1148 academics working in universities in the United Kingdom (UK) and representing all the major disciplines and career hierarchy. Respondents report an abundance of what we call 'afflictions' exacted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
535
3
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 663 publications
(673 citation statements)
references
References 23 publications
16
535
3
24
Order By: Relevance
“…From the viewpoint of Covid-19's disruptive nature, its impact has compelled rapid transformation in business processes and operational practices, e.g., the use of digital communication platforms (i.e. Zoom or MS Teams) and digital technologies for teaching and learning has now significantly grown in speed and scale, as compared to the glacial implementation during the pre-Covid-19 era (Bartik et al, 2020a;Watermeyer et al, 2020). According to Kamal and Choudrie (2020), prior to this pandemic, digitalization (or online collaboration) was being encouraged, but now, no more reinforcement is needed.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of Covid-19's disruptive nature, its impact has compelled rapid transformation in business processes and operational practices, e.g., the use of digital communication platforms (i.e. Zoom or MS Teams) and digital technologies for teaching and learning has now significantly grown in speed and scale, as compared to the glacial implementation during the pre-Covid-19 era (Bartik et al, 2020a;Watermeyer et al, 2020). According to Kamal and Choudrie (2020), prior to this pandemic, digitalization (or online collaboration) was being encouraged, but now, no more reinforcement is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have examined the impact of the COVID-19 emergency in universities, particularly on teaching, which is the most affected by the precautionary measures imposed by the governments of the States most affected by the pandemic. Precisely, the research carried out by Watermeyer et al (2020) in the Universities of the United Kingdom showed a dual reaction to the online migration by the academic body: "a ictions" for the competitiveness, sustainability within a global student market and, to a lesser extent, "affordances" in terms of accelerated pedagogical modernization on the level of social connectivity and inclusivity. The same study suggests extending the observation to other university contexts at an international level, as well as enlarging the object of research on the pedagogical dimension of technology (Watermeyer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the resilience notion has been conjugated mainly at the individual level to explain students withdrawal or retention (Cotton et al, 2017;Walker et al, 2006;Wellington et al, 2005). At the same time, the current COVID-19 pandemic has been emerging as a serious external disturbance that has hit HE organizations for their whole set of services -encompassing the Third Mission -thus stimulating a forthcoming debate on their responses in this respect (Watermeyer et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensification of performance demands on universities as players within an aggressively competitive, diversified and globally sprawling HE marketplacespecifically in relation to attracting and retaining students; in many sectors as high-paying customers has caused to reset the parameters of pedagogical praxis and alter expectations of academics as frontline educational providers. There is perhaps no greater evidence of the hold of consumer-demands over higher education pedagogy than what has been revealed through the COVID-19 pandemic, and widespread concerns that the physical closure of universities and a transition from face-to-face to online learning, teaching and assessment will discourage new applicants to universities and severely diminish revenue generated through tuition (Watermeyer, Crick, Knight, & Goodall, 2020).…”
Section: Competitive Accountability Versus Professional Accountabilitymentioning
confidence: 99%